Small and medium enterprise (SME) development in SAARC countries : challenges and policy reforms - SAARC Convention on SME Policy Reforms (2005 : Colombo, Sri Lanka); Gooneratne, Wilbert, 1938-; Hirashima, Shigemochi; Centre for Development Research (Sri Lanka); Federation of Chambers of Commerce & Industry of Sri Lanka; Friedrich-Naumann-Stiftung.; Small & Medium Enterprise Developers Project (Colombo : Centre for Development Research, 2006)
Contributed articles presented at SAARC Convention on SME Policy Reforms held at Colombo in December 2005 as a collaborative effort of CDR, FCCISL, SMED, and FNSt, Sri Lanka.
Includes statistics.
Includes bibliographical references.
Keywords: Small business -- Government policy -- South Asia -- Congresses; Small business -- Government policy -- South Asia -- Congresses -- Statistics